Role of HRUS in Detection and Localization of Foreign Bodies (TAJ: Journal of Teachers Association, 2010)
Prick injuries with metallic and non-metallic foreign body are commonly encountered cases in surgery and orthopedics OPD. Detection and localization is difficult task with conventional radiography. Ultrasonography, CT and MRI are other modes of evaluation but CT and MRI are expensive and not easily available.About 35 patients were evaluated with USG (7.5-10 MHz Linear probe) and X-ray for clinically suspicious non-radiopaque foreign body in soft tissue and extremities. Clinical presentation, symptoms anatomical location, and foreign body retrieved after surgery were recorded. X-ray detect only 3 foreign bodies where as HRUS detected 34 patient. Most of the cases FBs were present in ankle and foot. Majority of the foreign bodies were plant thorn and wood pieces. Plain X-ray is not sensitive for detection of non-radiopaque foreign bodies but USG is sensitive and specific for detection and localization in that cases.TAJ 2010; 23(1): 33-37